Low carbon development key issues - Urban, Frauke (London Routledge, 2013)
"This is the first comprehensive textbook to address the interface between international development and climate change in a carbon constrained world. It discusses the key conceptual, empirical and policy-related issues of low carbon development, taking an international and interdisciplinary approach to the subject by drawing on insights from across the sciences and social sciences whilst embedding the discussion in a global context. Written by an international team of leading academics and practitioners in low carbon development, this book is essential reading for students, academics, professionals and policy-makers interested in low carbon development and climate change policy"
Includes bibliographical references and index.
Keywords: Economic development -Environmental aspects